Melestarikan Prinsip-Prinsip Dasar Kehidupan sedulur sikep (Samin) dalam Keberagaman Budaya di Indonesia - Primandha Sukma Nur Wardhani; Samsuri Samsuri (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
The purpose of writing this article is to find out about the basic principles of life followed by sedulur sikep as part of the diversity of Javanese culture. Therefore there is a need for cultural preservation which is characterized by the basic principles of the life of the sedulur sikep. Articles compiled using the library research method is a data collection method that is carried out by utilizing library sources and materials. The result obtained is that sedulur sikep is a community group that still has and maintains its social foundation based on traditional values it adheres to. This community has a lot of local wisdom, among others, having a harmonious and sumeleh attitude, giving a good example of attitude, not talking (taking), not pethil (taking things), etc. The principle of harmony is not to like to be adored, not to get angry when reviled. The living person must: correct, be in harmony, understand others, behave cautiously, understand himself, be sensitive, patient, submit, and be mentally happy.